Competitiveness and Growth in Brazilian Cities Local Policies and Actions for Innovation - Ming Zhang (2010)
This report has been prepared by a team led by Ming Zhang, Lead Urban Economist in the Latin America and the Caribbean Region of the World Bank. The main authors are Ming Zhang (chapters 1, 2, 5, and Executive Summary); Mark Roberts, consultant and Lecturer at the University of Cambridge (chapter 1); Fernanda Ruiz NuÃ±ez, Young Professional at the World Bank (chapter 3); Daniel da Mata, consultant and Researcher at the Brazil Institute of Applied Economic Research (chapters 4 and 5); Monica Amorim, consultant and Professor at the Federal University of CearÃ¡ (chapter 4); Alec Hansen, consultant and President of the Economic Competitiveness Group, Inc.; Enrique Asturizaga, consultant; and Kim Cuenco, Senior Operations Officer at the World Bank Institute (chapter 5).